The United States, China and the freedom of the seas: Washington's FONOPs conflict with Beijing - Michael Paul (Stiftung Wissenschaft und Politik (SWP), 2016)
After several years of restraint, the United States conducted its latest freedom of navigation operation in the South China Sea on 22 January 2016. Three weeks later President Barack Obama hosted a conference of the ASEAN heads of state and government in California to discuss the opportunities for reducing tensions in the region, which is witnessing spiralling conflicts between China and its East Asian neighbours over island territories and their resources. Rather than contributing to a deescalation, China fanned the flames by stationing missile batteries on Woody Island, which is also claimed by Taiwan and Vietnam. Alongside that regional conflict, the South China Sea is also turning into an arena of conflict between Beijing and Washington. Amidst different interpretations of maritime law and the Convention on the Law of the Sea (UNCLOS), the question of whether the "freedom of the seas" is upheld or curtailed will have considerable geopolitical and strategic military consequences. (SWP Comments)
Keywords: 320